MODERN METHODS OF TEACHING ENGLISH TEACHING IN HIGHER EDUCATION - Ahmadjonova Guljahon; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The article discusses various strategies for teaching remote dialects in colleges. Particular attention was paid to decision-making strategies: coordination strategies, grammatical-translation, audiovisual, audio-linguistic and communicative. It is concluded that the communication strategy of is has begun to become the most dominant.